Design of a sustainable reverse supply chain in a remanufacturing environment: A case study of proton-exchange membrane fuel cell battery in Riyadh. (April 2019) - Alkahtani, Mohammed; Ziout, Aiman
This article presents the design for a sustainable reverse supply chain network for remanufacturing the proton-exchange membrane fuel cell used in hydrogen vehicles. An optimization model with multiple objectives is proposed. In this article, a multi-objective optimization model is proposed and used to design a near-optimal reverse supply chain network that satisfies economic, environmental, and societal objectives, which are combined into one multi-objective function. An end-of-life proton-exchange membrane fuel cell battery collection in Riyadh city is the subject of the designed network. This model is found to be capable of choosing collection centers (drop-off) from a set of available centers and selecting a facility location for the remanufacturing plant. The model also serves as a tool to carry out analyses under different scenarios, as well as future changes in the factors that influence the designed reverse supply chain network, such as the hydrogen tax credit and the CO2 emissions cap. The output of this research facilitates the transition from oil-dependent to renewable energy transportation by providing a solution for its end-of-life products. The output of this article is considered as preparedness plan to help countries who seek transition from oil-dependent transportation to a system that uses renewable energy.